THE SUITABILITY OF SHARIA LIFE INSURANCE POLICY FOR POJK NO. 69/POJK.05/2016 AND POJK NO. 72/POJK.05/2016 - Lathif, AH. Azharuddin; Habibaty, Diana Mutia (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
The increasing of sharia insurance companies have sprung up in Indonesia. However, in their policy contracts there are still some parts that are not in accordance with sharia principles. This mismatch can cause information distortion that can harm customers or sharia insurance participants. The Sharia Insurance Policy as a form of written contract between the insurance company and the customer or the insurance participant should duly follow sharia principles in order to avoid the elements that forbid it, therefore in Indonesia the policy making must follow the legislation, namely Financial Services Authority Regulation No.69 / POJK.05 / 2016 (hereinafter abbreviated as POJK No.69 / POJK.05 / 2016) and the Financial Services Authority Regulation No.72 / POJK.05 / 2016 (hereinafter abbreviated as POJK No.72 / POJK.05 / 2016) as the basis of the rule legislation describing the standardization of sharia policy contracts. This study uses qualitative methods, the data used in the form of primary, secondary, and non-legal materials. The technique used is in the form of content analysis with the theme of normative juridical research that analyzes legal principles and systematics, and how much the level of synchronization of ABC Islamic sharia insurance products at PT. XYZ against POJK No.69 / POJK.05 / 2016 and POJK No.72 / POJK.05 / 2016. The results of this study concluded that generally the ABC Islamic Sharia insurance policy PT. XYZ is in accordance with POJK No.69 / POJK.05 / 2016 and POJK No.72 / POJK.05 / 2016, but there are some peculiarities in this policy so that it still needs to be questioned about the welfare side.